2019
DOI: 10.1093/ejcts/ezy485
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pump-controlled retrograde trial off to arterio-venous bridging for weaning from venoarterial extracorporeal membrane oxygenation†

Abstract: OBJECTIVES The aim of the study is to compare a technique of pump-controlled retrograde trial off (PCRTO) to insertion of an arterio-venous (AV) bridge to conduct a trial from venoarterial extracorporeal membrane oxygenation (VA ECMO). METHODS We studied all patients who were weaned from VA ECMO using either PCRTO or AV bridging from November 2014 to April 2018. Demographic data, indications for ECMO, duration of ECMO, durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…Over the recent decades since the widespread utilization of V-A ECMO, multiple weaning strategies exist, of which decremental pump ow reduction and arteriovenous bridging recirculation technique are the mainstream approaches [2][3][4][5][6][7][8][9][10] . Nevertheless, variations in practice exist among institutions, and there are no consensus guidelines to standardize the weaning algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the recent decades since the widespread utilization of V-A ECMO, multiple weaning strategies exist, of which decremental pump ow reduction and arteriovenous bridging recirculation technique are the mainstream approaches [2][3][4][5][6][7][8][9][10] . Nevertheless, variations in practice exist among institutions, and there are no consensus guidelines to standardize the weaning algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…1). An APTT at 1.5-2.5 times the normal value had to be attained before initiation of PCRTO 9,10,12,13 , a bolus of unfractionated heparin would be given if the target clotting pro le is not met. The sweep gas ow to the oxygenator is turned off once the retrograde ECMO ow is achieved.…”
Section: Pcrto Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…They compared the results between the arteriovenous bridge group (n = 20) and the PCRTO group (n = 31), which expanded the study in 2019. 13 They reported that PCRTO is a safe, simple, and reproducible procedure while preserving the circuit in pediatric patients. In adult patients, there has been also an effort to check cardiovascular capacity under full cardiac loading before VA ECMO weaning.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports have been published on pump controlled retrograde trial off (PCRTO). [1][2][3][4][5][6] During PCRTO, the pump speed is reduced to the point where the patient can eject into the arterial cannula, effectively reversing the veno-arterial flow into an arteriovenous shunt. This leads to a temporary cessation of cardiorespiratory ECMO (extracorporeal membrane oxygenation) support without the need to clamp, introduce a 'bridge' or risk blood stasis in the circuit.…”
Section: To the Editormentioning
confidence: 99%